Polityka tożsamości literatury polskiej. Żydówka – obcość nieprzekraczalna w „Wielkim Tygodniu” Jerzego Andrzejewskiego i „Przy torze kolejowym” Zofii Nałkowskiej - Ratajska, Patrycja (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
According to the concept coined by B enedict Anderson, literature is one of the major instruments of building identity of imagined communities. For every narrative identity essential element is the figure of stranger. The paper is devoted to the reconstruction of the image of Jewess in polish literature. In the identity discourse of polish culture she acts as eternal stranger.